A region of the 85-kilodalton (kDa) subunit of phosphatidylinositol 3-kinase binds the 110-kDa catalytic subunit in vivo. - Klippel, A (1993)
Phosphatidylinositol (PI) 3-kinase is a heterodimer consisting of an 85-kDa subunit (p85) and 110-kDa subunit (p110). The 85-kDa noncatalytic subunit, which contains two Src homology 2 (SH2) domains, one SH3 domain, and a domain homologous to the carboxy terminus of the breakpoint cluster region gene product, is known to mediate the association of the PI 3-kinase complex with activated growth factor receptors. We previously demonstrated that the C-terminal SH2 domain of p85 is responsible for the interaction of PI 3-kinase with phosphorylated platelet-derived growth factor receptor. To define the region in p85 that directs the complex formation with the PI 3-kinase catalytic subunit, a series of truncated p85 mutants was analyzed for association with p110 in vivo. We found that a fragment of p85 containing the region between the two SH2 domains was sufficient to promote the interaction with p110 in vivo. The complex between the fragment of p85 and p110 had PI 3-kinase activity that was comparable in magnitude to the activity of p110 associated with full-length p85. The binding with p110 was abolished when this domain in p85 was disrupted. These results identify a novel structural and functional element that is responsible for localizing the catalytic subunit of PI 3-kinase.